Demoralization during the Italian quarantine due to 2019 coronavirus disease pandemic: prevalence and association with psychological well-being and coping strategies. Issue 2 (7th February 2023) - Botto, Rossana; Galante, Marco; Miniotti, Marco; Leombruni, Paolo
ABSTRACT: The aims of the study were to investigate demoralization in a sample of Italian citizens during the Italian quarantine due to COVID-19 pandemic and to explore its associations with psychological well-being, coping strategies, participants' socio-demographic characteristics and COVID-19-related factors. Italian citizens aged over 18 and quarantined in Italy were recruited. A cross-sectional online survey was launched through a snow-ball sampling and 1123 surveys were collected. Participants answered ad hoc questions and completed the Psychological General Well-Being Index, the Demoralization Scale, and the Coping Orientation to Problems Experienced-New Italian Version. Disheartenment, dysphoria, and sense of failure were the subdimensions of demoralization with higher scores. Demoralization was associated with depressed mood, positive well-being, self-control, general health, vitality, problem-solving, and avoidance and religious coping strategies. Individuals who were female, older, without children and not working during quarantine had higher demoralization. Quarantine-related changes can elicit demoralization that is associated to lower psychological well-being. Problem-solving and religious coping can protect against demoralization, while avoidant coping strategies can exacerbate it. Assessing and treating demoralization, especially in the categories of citizens most at risk of developing it, could be useful to provide adequate care against COVID-19-related distress.